Ты - моя половинка: [роман] / Елена Вернер - Вернер Елена (Верю, надеюсь, люблю, 2016)
Экземпляры: ф.4 (20160608) / Инвентарный номер: 57022 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 35 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44